Of gods and men [videorecording (DVD)] = Des hommes et des dieux - Herlin, Jacques, 1927-2014; Wilson, Lambert; Lonsdale, Michaël, 1931-2020-; Beauvois, Xavier (Sony Pictures Classics, 2011)
Eight French Christian monks live in harmony with their Muslim brothers in a monastery in the mountains of North Africa in the 1990's. When a crew of foreign workers are massacred by an Islamic fundamentalist group, fear sweeps though the region. The army offers them protection, but the monks refuse. Should they leave? Despite the growing menace in their midst, they slowly realize that they have no choice but to stay, come what may. Includes bonus features.